1985
DOI: 10.1037/0022-0167.32.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Counseling expectations of clients and nonclients for group and individual treatment modes.

Abstract: The present investigation compared expectations held by male and female clients and nonclients for group and individual counseling modes. These expectations were measured by the Expectations About Counseling questionnaire (Tinsley, Workman, & Kass, 1980). Results indicated significant differences between the two modes, the sexes, and the two populations (clients and nonclients); however, no interaction effects were noted. Results are discussed in terms of how differential beliefs about group and individual cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1
3

Year Published

1990
1990
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 17 publications
2
25
1
3
Order By: Relevance
“…These observed gender differences in expectations about counseling are consistent with the findings of previous studies in which women have been found to have higher scores than men and as a result provide additional support for the belief that men and women approach the counseling relationship with different expectations (Brown, Frey, & Carpo, 1972;Kemp, 1994;Pecnik & Epperson, 1985;Subich & Coursol, 1985;Subich & Hardin, 1985;Tinsley & Harris, 1976;Tinsley, Hinson, Holt, & Tinsley 1990;Tinsley, Workman, & Kass, 1980). In fact, these findings are identical to those of Pecnik and Epperson (1 985).…”
Section: Discussionsupporting
confidence: 88%
“…These observed gender differences in expectations about counseling are consistent with the findings of previous studies in which women have been found to have higher scores than men and as a result provide additional support for the belief that men and women approach the counseling relationship with different expectations (Brown, Frey, & Carpo, 1972;Kemp, 1994;Pecnik & Epperson, 1985;Subich & Coursol, 1985;Subich & Hardin, 1985;Tinsley & Harris, 1976;Tinsley, Hinson, Holt, & Tinsley 1990;Tinsley, Workman, & Kass, 1980). In fact, these findings are identical to those of Pecnik and Epperson (1 985).…”
Section: Discussionsupporting
confidence: 88%
“…The majority of studies on client expectations about counseling have used undergraduate students drawn from psychology classes rather than actual clients. Three studies were located that used actual clients, although two of these studies still used college students (Subich & Coursol, 1985;H. E. A. Tinsley, Tokar, & Helwig, 1994) and only one of the studies used clients from the community (Satterfield et al, 1995).…”
Section: Variable Bmentioning
confidence: 99%
“…Tinsley & Harris, 1976); status as a college student or client (Subich & Coursol, 1985); level of psychosocial development (D. J. Tinsley, Hinson, Holt, & Tinsley, 1990); stages of the change process (Satterfield et al, 1995); gender (H. E. A.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Women also expect more immediacy in the counseling process than do men, whereas men expect more directiveness (Hardin & Yanico, 1983;H. E. A. Tinsley & Harris, 1976) and more self-disclosure from the counselor (Hardin & Yanico, 1983;Subich & Cursol, 1985).…”
Section: Expectations About Counselingmentioning
confidence: 99%